2020
DOI: 10.1002/cam4.3450
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a multigene testing for preoperative evaluation of indeterminate thyroid nodules: A prospective blinded single center study in China

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…In the literature, Nikiforov et al also reported that only one of three TSHR mutation-positive nodules was identified as cancer after surgery and two NRAS -mutated samples were benign on histology ( 30 ). Furthermore, RAS mutations are considered to be not specifically associated with malignant (75–88%) or potentially malignant outcomes ( 7 , 27 , 31 , 32 , 33 ) and are highly predictive of predominantly low-risk follicular-pattern carcinomas ( 34 ), which is further supported by our results of a significantly lower frequency of lymph node metastasis in RAS -mutated malignancies. Additional gene mutations including SPOP , EZH1 , and ZNF148 are also suggested to be benign markers ( 32 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the literature, Nikiforov et al also reported that only one of three TSHR mutation-positive nodules was identified as cancer after surgery and two NRAS -mutated samples were benign on histology ( 30 ). Furthermore, RAS mutations are considered to be not specifically associated with malignant (75–88%) or potentially malignant outcomes ( 7 , 27 , 31 , 32 , 33 ) and are highly predictive of predominantly low-risk follicular-pattern carcinomas ( 34 ), which is further supported by our results of a significantly lower frequency of lymph node metastasis in RAS -mutated malignancies. Additional gene mutations including SPOP , EZH1 , and ZNF148 are also suggested to be benign markers ( 32 ).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, RAS mutations are considered to be not specifically associated with malignant (75–88%) or potentially malignant outcomes ( 7 , 27 , 31 , 32 , 33 ) and are highly predictive of predominantly low-risk follicular-pattern carcinomas ( 34 ), which is further supported by our results of a significantly lower frequency of lymph node metastasis in RAS -mutated malignancies. Additional gene mutations including SPOP , EZH1 , and ZNF148 are also suggested to be benign markers ( 32 ). Therefore, additional features are needed for a more accurate malignancy prediction in thyroid nodules with TSHR , NRAS , or some ‘low-risk’ gene mutations.…”
Section: Discussionsupporting
confidence: 80%
“…Below, two of these latter studies that focused on the clinical output of the custom panels along with their analytical performance are discussed in detail [19,23]. Song et al designed a custom NGS panel, the FSZ-Thyroid NGS panel, covering at least 1000 hotspots in 16 thyroid-cancer-related genes, including the AKT1, BRAF, CTNNB1, EIF1AX, EZH1, GNAS, HRAS, KRAS, NRAS, PIK3CA, RET, SPOP, TERT, TP53, TSHR and ZNF148 genes.…”
Section: From Single Gene Testing To Parallel and Massive Sequencing Analysismentioning
confidence: 99%
“…Song et al designed a custom NGS panel, the FSZ-Thyroid NGS panel, covering at least 1000 hotspots in 16 thyroid-cancer-related genes, including the AKT1, BRAF, CTNNB1, EIF1AX, EZH1, GNAS, HRAS, KRAS, NRAS, PIK3CA, RET, SPOP, TERT, TP53, TSHR and ZNF148 genes. This panel was adopted to process a prospective series of 196 indeterminate FNAs (153 AUS/FLUS and 43 FN/SFN) [23]. High-quality nucleic acids were extracted from cells obtained by a dedicated pass.…”
Section: From Single Gene Testing To Parallel and Massive Sequencing Analysismentioning
confidence: 99%
See 1 more Smart Citation